MEMO Organisation Modelling Language (1): Focus on organisational structure - Ulrich Frank (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2011)
Organisation models are at the core of enterprise model, since they represent key aspects of a company's action system. Within MEMO, the Organisation Modelling Language (OrgML) supports the construction of organisation models. They can be divided into two main abstractions: a static abstraction is focusing on the structure of an organisation that reflects the division of labour with respect to static responsibilities and a dynamic abstraction that is focusing on models of business processes. In this report, those concepts of the OrgML are presented that serve modelling static aspects of an organisation. They cover prevalent concepts used in organisational charts as well as concepts required for specifying temporal units of work, roles and committees. The description of these modelling concepts comprises three parts: A meta model serves to specify the abstract syntax and semantics. A language description includes an overview of all concepts and the corresponding notational elements (concrete syntax). Finally, the use of the concepts is illustrated through various examples.
Keywords: 650